2021
DOI: 10.1590/1516-3180.2021.0113.r1.0504221
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19 repercussions in ophthalmology: a narrative review

Abstract: The outbreak of the new coronavirus (COVID-19) that started in Wuhan, China, has spread all over the world and has had a great impact on eye care. 1 It is a ribonucleic acid (RNA) virus, called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which may have ocular manifestations in some patients. 2 This is a single-stranded RNA virus with a genome of about 30 kb in length. The RNA genome encodes its proteins. The proteins are spike protein S, membrane protein M, envelope protein E and nucleocapsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…O tempo despendido em frente às telas tem sido considerado importante indicador de atividades sedentárias e está associado a inúmeros problemas de saúde, que incluem o comportamento sedentário e o excesso de peso corporal 17 . A utilização do computador para trabalho e estudo estão vinculados às tarefas leitura, pesquisas e aulas, elaboração de atividades, participação em reuniões, debates e seminários, no qual faz parte de serviços dos professores e que estabelece o uso das tecnologias digitais no momento da pandemia, colaborando para o aumento do tempo sentado 16 .…”
Section: Discussionunclassified
“…O tempo despendido em frente às telas tem sido considerado importante indicador de atividades sedentárias e está associado a inúmeros problemas de saúde, que incluem o comportamento sedentário e o excesso de peso corporal 17 . A utilização do computador para trabalho e estudo estão vinculados às tarefas leitura, pesquisas e aulas, elaboração de atividades, participação em reuniões, debates e seminários, no qual faz parte de serviços dos professores e que estabelece o uso das tecnologias digitais no momento da pandemia, colaborando para o aumento do tempo sentado 16 .…”
Section: Discussionunclassified
“…Among the various symptoms presented, it is noteworthy that postural control can be highly susceptible to alterations as it depends on the coordinated integration of sensory systems (visual, vestibular, and somatosensory) and the musculoskeletal system, which can present important sequelae in the long COVID-19. Although the predominant ocular manifestation during the acute phase of SARS-CoV-2 infection is conjunctivitis, it is clear that other ophthalmologic manifestations are present in the long term ( 17 ), such as loss of corneal nerve fibers, and significant changes in the pupillary response to light and impairment of pupillary microcirculation have also been observed in long COVID-19 ( 18–21 ). Some authors have shown that SARS-CoV-2 infection can spread to the middle and inner ear, causing an inflammatory response or direct effect on the epithelium, resulting in symptoms related to hearing and balance ( 22–25 ).…”
Section: Introductionmentioning
confidence: 99%
“…inversão, onde ocorre simultaneamente com os movimentos de inversão e adução do tornozelo em flexão plantar e isso gera danos tanto nos ligamentos laterais tendo como consequência rompimento de fibras ligamentares o qual pode ser dividida em lesão de primeiro, segundo e terceiro grau [5][6][7][8][9] De acordo com a epidemiologia ocorrem todos os dias uma entorse de tornozelo para cada 10.000 habitantes. Um estudo sobre o trauma no tornozelo foi concluído que as entorses mais frequentes são em jovens e a maioria do sexo masculino.…”
unclassified